Cloud Computing: Market Trends and Future Research Directions - Kumar, Praveen; Bade, Shailendra (Journal of Global Economy, Business and Finance, 2025)
Distributed computing is a quickly creating and great promising innovation. It has stirred the worry of the PC society of entire world. Distributed computing is Web based registering, by which shared data, assets, and programming, are given to terminals and convenient gadgets on-request, similar to the energy framework. Cloud computing is the product of the combination of grid computing, distributed computing, parallel computing, and ubiquitous computing. It aims to build and forecast sophisticated service environment with powerful computing capabilities through an array of relatively low-cost computing entity, and using the advanced deployment models like SaaS (Software as a Service), PaaS (Platform as a Service), IaaS (Infrastructure as a Service), HaaS (Hardware as a Service) to distribute the powerful computing capacity to end-users. This paper will investigate the foundation and administration models and furthermore presents the current examination issues and suggestions in distributed computing like security, unwavering quality, protection, etc.